Functional business valuation – purpose is king! - Christian Toll; Thomas Hering (Managerial Economics)
In the present contribution, we discuss the basic principles of functional business valuation. In addition to a distinction between objective and subjective valuation theory, the differences between finance-theoretical and investment-theoretical valuation approaches are worked out. The core of our discussion is devoted to an overview of the three main functions and value concepts of functional business valuation theory.